The Reality of Organizational Development in the Student Activities Department at the University of Babylon from the Perspective of the Employees - Diyar Fakhrulddin Mohammed; Waleed Ganim Malik; Khalid Hamad Naser (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This research aims to develop the work of the Student Activities Department at the University of Babylon by identifying the current state of the department and assessing the adequacy of its material and human resources to achieve its objectives. The researchers defined their research population through a comprehensive survey of all employees involved in sports and university activities across all 20 colleges of the University of Babylon, totaling 126 employees. The researchers applied and processed the research data using the SPSS statistical software. The most important findings indicated that intensive training courses and the updating of work methods directly contribute to raising employee efficiency. Furthermore, the researchers found that employees possess a suitable academic background, particularly graduates of physical education and sports, which helps and enhances the department's ability to achieve its goals. The research also revealed that a culture of change among employees is a necessary and fundamental condition for the success of the development program. The researchers recommended establishing continuous training programs based on the latest advanced administrative methods and implementing a system of financial and in-kind incentives for employees based on performance evaluations and efficiency. The function of employees is to implement awareness campaigns and programs in order to work on changing behavior in order to eliminate resistance to change and promote the institutional values of employees.